2021
DOI: 10.1146/annurev-environ-012220-022716
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Worry, and Grief in a Time of Environmental and Climate Crisis: A Narrative Review

Abstract: Climate change worry, eco-anxiety, and ecological grief are concepts that have emerged in the media, public discourse, and research in recent years. However, there is not much literature examining and summarizing the ways in which these emotions are expressed, to what processes they are related, and how they are distributed. This narrative review aims to ( a) summarize research about the relationships between, on the one hand, negative emotions in relation to climate change and other environmental problems and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
205
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(304 citation statements)
references
References 126 publications
5
205
1
4
Order By: Relevance
“…Climate anxiety could be mitigated by constructive and accurate climate change narratives that underline how to cope with it [10]. The risk of overexposure and the existence of excessive climate disaster content could result in eco-paralysis, as described by Albrecht [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Climate anxiety could be mitigated by constructive and accurate climate change narratives that underline how to cope with it [10]. The risk of overexposure and the existence of excessive climate disaster content could result in eco-paralysis, as described by Albrecht [38].…”
Section: Discussionmentioning
confidence: 99%
“…These effects include an increase in mortality rates and injuries resulting from natural disasters and other extreme weather events, and an increased risk of malnutrition, physical illness, and psychological distress [6][7][8]. The relationship between acute meteorological disasters, such as floods, heat waves, and cyclones, and the subsequent anxiety experienced, is particularly well-documented [9][10][11][12], evidencing the threat of climate change to the mental health of individuals. Ogunbode et al [13] showed that mental health and psycho-social well-being can be influenced both directly, for example, through life experiences related to extreme weather events or natural disasters, and indirectly, through exposure to climate change news.…”
Section: Introductionmentioning
confidence: 99%
“…10,45 In fact, anxiety can act as a source of efficacy beliefs and motivation for change. 46 However further research is needed to understand underlying mechanisms in larger and diverse samples.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a 2021 survey of 76,328 Facebook users in 31 countries spanning all the inhabited continents showed that most respondents were "somewhat" or "very" worried about climate change (Leiserowitz et al, 2021). As the acute and long-term effects of climate change become a lived experience for a growing proportion of the world's population, there also appears to be a corresponding rise in the number of people experiencing psychological distress in relation to the environmental and climate crisis (Ojala et al, 2021;Pihkala, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Commonly termed "eco-anxiety" or "climate anxiety", the experience of environment-related distress encompasses negative emotions like fear, worry, anger, guilt, shame, hopelessness and despair (Marks et al, 2021;Ojala et al, 2021). It has been noted that anxiety has simply emerged as a concept used by researchers to represent a wide range of negative emotions people have regarding climate change (Clayton, 2020).…”
Section: Introductionmentioning
confidence: 99%